Microbial Phagocytic Receptors and Their Potential Involvement in Cytokine Induction in Macrophages - Fu, Yan Lin; Harrison, Rene E. (Frontiers in Immunology, 2021)
Phagocytosis is an essential process for the uptake of large (>0.5 m) particulate matter including microbes and dying cells. Specialized cells in the body perform phagocytosis which is enabled by cell surface receptors that recognize and bind target cells. Professional phagocytes play a prominent role in innate immunity and include macrophages, neutrophils and dendritic cells. These cells display a repertoire of phagocytic receptors that engage the target cells directly, or indirectly via opsonins, to mediate binding and internalization of the target into a phagosome. Phagosome maturation then proceeds to cause destruction and recycling of the phagosome contents. Key subsequent events include antigen presentation and cytokine production to alert and recruit cells involved in the adaptive immune response. Bridging the innate and adaptive immunity, macrophages secrete a broad selection of inflammatory mediators to orchestrate the type and magnitude of an inflammatory response. This review will focus on cytokines produced by NF-κB signaling which is activated by extracellular ligands and serves a master regulator of the inflammatory response to microbes. Macrophages secrete pro-inflammatory cytokines including TNFα, IL1β, IL6, IL8 and IL12 which together increases vascular permeability and promotes recruitment of other immune cells. The major anti-inflammatory cytokines produced by macrophages include IL10 and TGFβ which act to suppress inflammatory gene expression in macrophages and other immune cells. Typically, macrophage cytokines are synthesized, trafficked intracellularly and released in response to activation of pattern recognition receptors (PRRs) or inflammasomes. Direct evidence linking the event of phagocytosis to cytokine production in macrophages is lacking. This review will focus on cytokine output after engagement of macrophage phagocytic receptors by particulate microbial targets. Microbial receptors include the PRRs: Toll-like receptors (TLRs), scavenger receptors (SRs), C-type lectin and the opsonic receptors. Our current understanding of how macrophage receptor stimulation impacts cytokine production is largely based on work utilizing soluble ligands that are destined for endocytosis. We will instead focus this review on research examining receptor ligation during uptake of particulate microbes and how this complex internalization process may influence inflammatory cytokine production in macrophages.